2021
DOI: 10.31254/dentistry.2021.6204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and gender differences of buccally displaced canines of 12 years school children and 18-23 years adults in Shah-Alam, Malaysia

Abstract: Background: The buccally displaced canines (BDC) are more commonly encountered conditions in orthodontic clinics. It is a positional variation result of several factors such as retained deciduous canines, crowding, and lateral incisors anomalous. Aims: To determine the prevalence and gender differences of one-two-three-four buccally displaced canines in the area of Shah-Alam, Malaysia. Methods: A cross-sectional study of 399 subjects; was consist of two age groups; 208 subjects of school children aged 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…26,28 A previous study revealed that determining the occlusal features at early permanent dentition would have a significant role in modifying the preventive and interceptive treatment plans. 29,30 Assessing the prevalence of malocclusion in children and adults may reduce or eliminate future treatment needs, reduce the treatment cost, and plan preventive and curative measures. 31 Moreover, it is also important for resource planning and funding.…”
mentioning
confidence: 99%
“…26,28 A previous study revealed that determining the occlusal features at early permanent dentition would have a significant role in modifying the preventive and interceptive treatment plans. 29,30 Assessing the prevalence of malocclusion in children and adults may reduce or eliminate future treatment needs, reduce the treatment cost, and plan preventive and curative measures. 31 Moreover, it is also important for resource planning and funding.…”
mentioning
confidence: 99%